THE ROLE OF TASK-INDUCED INVOLVEMENT IN VOCABULARY LEARNING OF IRANIAN LANGUAGE LEARNER - Fatemeh Khonamri; Zahra Hamzenia (English Review: Journal of English Education, 2013)
Abstract: This study investigated Laufer and Hustijnâ€™s (2001) Involvement Load Hypothesis in vocabulary learning. It comprised two experiments. Experiment 1 examined whether two tasks with equal involvement load but different distribution of components would yield the same result in initial learning and retention of target words. Experiment 2 investigated whether two tasks, one input and another output, with equal involvement load and the same distribution of components would result in equivalent initial learning and retention of target words. 126 advanced English learners completed one of three vocabulary learning tasks that equated in the amount of involvement they induced: sentence writing, ï¬ll-in, and translation (L2-L1). The result of t-test for Experiment 1 showed that when two tasks had equal involvement load but different distribution of components they resulted in similar amounts of initial learning and retention of new words. The ï¬ndings of Experiment 2 indicated when two tasks, one input and another output, had equal involvement load and the same distribution of components., they led to superiority of ï¬ll-in task over translation task in initial vocabulary learning, however, not in retention of newÂ  words. Key Words: involvement load hypothesis; incidental vocabulary learning; depth of processing theory